login
The OEIS Foundation is supported by donations from users of the OEIS and by a grant from the Simons Foundation.

 

Logo


Hints
(Greetings from The On-Line Encyclopedia of Integer Sequences!)
A100238 G.f. A(x) satisfies: 2^n + 1 = Sum_{k=0..n} [x^k] A(x)^n for n>=1. 3
1, 2, -2, 4, -12, 40, -144, 544, -2128, 8544, -35008, 145792, -615296, 2625792, -11311616, 49124352, -214838528, 945350144, -4182412288, 18593224704, -83015133184, 372090122240, -1673660915712, 7552262979584, -34178799378432, 155096251351040, -705533929816064 (list; graph; refs; listen; history; text; internal format)
OFFSET

0,2

LINKS

Table of n, a(n) for n=0..26.

FORMULA

a(n) = (-2*(2*n-3)*a(n-1) + 4*(n-3)*a(n-2))/n for n>2, with a(0)=1, a(1)=2, a(2)=-2.

G.f.: A(x) = (1+2*x + sqrt(1+4*x-4*x^2))/2.

G.f. satisfies: (2+z)^n + (1+z)^n - z^n = Sum_{k=0..n} [x^k] (A(x)+z*x)^n for all z, where [x^k] F(x) denotes the coefficient of x^k in F(x).

Given g.f. A(x), then B(x)=A(x)-1-x series reversion is -B(-x). - Michael Somos, Sep 07 2005

Given g.f. A(x) and C(x) = g.f. of A025225, then B(x)=A(x)-1-x satisfies B(x)=x-C(x*B(x)). - Michael Somos, Sep 07 2005

G.f.: 4x^2/(1+2x - sqrt(1+4x-4x^2)). - Michael Somos, Sep 08 2005

EXAMPLE

From the table of powers of A(x), we see that

2^n+1 = Sum of coefficients [x^0] through [x^n] in A(x)^n:

A^1: [1, 2], -2, 4, -12, 40, -144, 544, -2128, 8544, ...;

A^2: [1, 4, 0], 0, -4, 16, -64, 256, -1040, 4288, ...;

A^3: [1, 6, 6, -4], 0, 0, -8, 48, -240, 1120, -5088, ...;

A^4: [1, 8, 16, 0, -8], 0, 0, 0, -16, 128, -768, ...;

A^5: [1, 10, 30, 20, -20, -8], 0, 0, 0, 0, -32, ...;

A^6: [1, 12, 48, 64, -12, -48, 0], 0, 0, 0, 0, 0, ...;

A^7: [1, 14, 70, 140, 56, -112, -56, 16], 0, 0, 0, ...;

A^8: [1, 16, 96, 256, 240, -128, -256, 0, 32], 0, 0, ...; ...

In the above table of coefficients in A(x)^n, the main diagonal satisfies:

[x^n] A(x)^(n+1) = (n+1)*A009545(n+1) for n>=0.

PROG

(PARI) {a(n)=if(n==0, 1, (2^n+1-sum(k=0, n, polcoeff(sum(j=0, min(k, n-1), a(j)*x^j)^n+x*O(x^k), k)))/n)}

(PARI) {a(n)=if(n==0, 1, if(n==1, 2, if(n==2, -2, (-2*(2*n-3)*a(n-1)+4*(n-3)*a(n-2))/n)))}

(PARI) {a(n)=polcoeff( (1+2*x+sqrt(1+4*x-4*x^2+x^2*O(x^n)))/2, n)}

(PARI) a(n)=polcoeff((1+2*x+sqrt(1+4*x-4*x^2+x*O(x^n)))/2, n)

CROSSREFS

Cf. A100223, A071356, A009545, A143045.

a(n) = -(-1)^n * A025227(n), if n>1.

Sequence in context: A288303 A287604 A007181 * A208529 A212660 A098774

Adjacent sequences:  A100235 A100236 A100237 * A100239 A100240 A100241

KEYWORD

sign

AUTHOR

Paul D. Hanna, Nov 30 2004

STATUS

approved

Lookup | Welcome | Wiki | Register | Music | Plot 2 | Demos | Index | Browse | More | WebCam
Contribute new seq. or comment | Format | Style Sheet | Transforms | Superseeker | Recent
The OEIS Community | Maintained by The OEIS Foundation Inc.

License Agreements, Terms of Use, Privacy Policy. .

Last modified May 15 06:16 EDT 2021. Contains 343909 sequences. (Running on oeis4.)